Analisis Sentimen Terhadap Kendaraan Listrik di Indonesia Menggunakan Metode Klasifikasi Naïve Bayes - Farhani, Aulia; Sutisna (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Indonesians' awareness of environmental issues and carbon emission reduction is driving interest in electric vehicles as eco-friendly transportation. The Indonesian government supports the transition from conventional vehicles to electric vehicles to reduce carbon and greenhouse gas emissions, as seen by the significant increase in the use of electric vehicles from 2021 to 2023. Ministry of Industry data shows this increase, supported by Presidential Regulation No. 79 of 2023. While electric vehicles offer benefits such as zero emissions and high efficiency, challenges such as limited charging infrastructure still exist. Public response is mixed, influenced by environmental awareness, government incentives, and technology. To understand public sentiment, this study uses sentiment analysis from social media X (Twitter) with the Naïve Bayes method. The test results show an accuracy of 84.13%, with a recall of 92.70% positive sentiment and 50.00% negative sentiment. Precision of positive sentiment reaches 88.06%, while negative sentiment is 63.27%. With a total of 2,468 datasets, 2,198 data were predicted as positive sentiment and 298 as negative sentiment. This research aims to provide an understanding of public sentiment towards electric vehicles, helping the government and the automotive industry in designing policies and promotions.